MENINGKATKAN KINERJA PEMASARAN UMKM MELALUI PERAN LINGKUNGAN, INOVASI PRODUK DAN KREATIFITAS STRATEGI PEMASARAN - Gendut sukarno (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The role of the ability to adapt with the environment, superior creativity marketing strategy and product innovation are necessary in order to maximize the achievement of performance marketing.This research aims to study the concept of the Environmental Role, Creative Marketing Strategies, Product Innovation of Small and Medium Enterprise Performance Marketing (UKM) in managing its business, is expected to help the Department of Cooperatives and Micro Small and Medium Enterprise in Sidoarjo district adopted a policy about empowering UMKM. The sample in this study are UKM's producer of bag and suitcase in Kendensari, Tanggulangin-Sidoarjo as many as 100 people. The analysis technique used is the Structural Equation Model (SEM). Results found that  the environment has no significant effect on product innovation but the environment has a significant positive effect on creative marketing strategies, while creative marketing strategy has no significant  effect on the performance of marketing and product innovation has a significant positive effect on marketing performance